Emergency Care and Medicine: Update on the Journal’s Definition, Aim, Scope, Requirements, and Recommendations for 2025 - Raimundas Lunevicius (Emergency Care and Medicine)
After organisational and preparatory work in 2023, Emergency Care and Medicine (ECM) was launched in 2024, culminating in the journal’s formal recognition by the Directory of Open Access Journals (DOAJ) on 17 January 2025, https://doaj [...]